Computational Study of Doping in Dopamine with Halogens to Control Optical and Spectroscopic Properties - Nasidi, Ibrahim Isah; Orek, Cahit; Majid, Abdul; Eldin, Sayed M.; Kaygili, Omer; Bulut, Niyazi (Amer Chemical Soc, 2023)
In this research, a comprehensive study of dopamine wasconductedusing the theoretical first principles method due to its crucial importanceas a hormone for the neurotransmission process in the animal body.Many basis sets and functionals were used for optimization of thecompound to attain stability and find the appropriate energy pointfor the overall calculations. Then, the compound was doped with thefirst three members of the halogen family (fluorine, chlorine, andbromine) to analyze the effect of their presence in terms of changein their electronic properties, such as band gap and density of states,and spectroscopic parameters, such as nuclear magnetic resonance andFourier transform infrared. It was found that the band gap of thesystem changes depending on the doping of halogens.
Keywords: Aqueous-Solution; 3,4-Dihydroxyphenyl Derivatives; Free-Energies; Gas-Phase; Complexes; Catecholamines; Continuum; Acid; Conformation; Equilibrium